Convergence time to equilibrium distributions of autonomous and periodic non-autonomous graphs - Silva, Teresa (2017)
We present some estimates of the time of convergence to the equilibrium distribution in autonomous and periodic non-autonomous graphs, with ergodic stochastic adjacency matrices, using the eigenvalues of these matrices. On this way we generalize previous results from several authors, that only considered reversible matrices.